Aplikasi Pencarian Lokasi Agen Pos Di Surabaya Berbasis Android - Eko Sulaiman (Melek IT : Information Technology Journal, 2019)
Mobile technology is one of the technologies that are now growing rapidly and much sought after. In this case, technology can make it easier for users to communicate and obtain information. Mobile technology can also be combined with GPS, so it can provide information and instructions to find a location for the user. The current information needs much needed by many among the public. One of the required information, namely the postal agent locations search application in surabaya, so that it can help users as well as newcomers from out of town who are less know location of postal agent in surabaya. Using Android-based Mobile application, then the user can be expected to be able to operate the application.